Answer:
(2, 3 )
Step-by-step explanation:
Given the 2 equations
2x - 3y = - 5 → (1)
5x + 4y = 22 → (2) [ rearranged equation ]
Multiplying (1) by 4 and (2) by 3 and adding will eliminate the term in y
8x - 12y = - 20 → (3)
15x + 12y = 66 → (4)
Add (3) and (4) term by term to eliminate y, that is
23x = 46 ( divide both sides by 23 )
x = 2
Substitute x = 2 in either of the 2 equations and evaluate for y
Substituting into (2)
5)2) + 4y = 22
10 + 4y = 22 ( subtract 10 from both sides )
4y = 12 ( divide both sides by 4 )
y = 3
Solution is (2, 3 )
X is -2 because you add x to both sides, then you subtract 6 from both sides and you get x=-2
4x+y = 3
if x = 0, y = 3
ordered pair (0,3)
Answer:
1130.97
Step-by-step explanation:
It was easy!
Answer: 0.0052
Step-by-step explanation:
Total number of times experiment was performed (n)= 12
Probability of the event (that one key out of a total of 12 opens the door) = 1/12 = 0.083
Hence, p = 0.83
q = 1 - p = 11/12 = 0.917
x = 3
Since the experiment was performed n number of times, a binomial probability distribution can defined the experiment.
P(x=r) = nCr ×p^r × q^n-r
P(x=3) = 12C3 × (0.083)⁴ × (0.917)^8
P(x=3) = 220 × (0.083)⁴ × (0.917)^8
P(x=3) = 0.0052